Review of the Psychological and Neural Evidence Concerning the Uncanny Valley Theory - Casas Arias, Miguel (Street Art & Urban Creativity, 2025)
This article reviews the psychological and neuroscientific evidence concerning the Uncanny Valley theory, originally proposed by Masahiro Mori in 1970. The theory posits that human affinity towards robots increases with their realism, but only up to a certain point, beyond which emotional responses become markedly negative. Neuroimaging studies suggest that this phenomenon stems from perceptual conflicts within the brain. Recent technological advances have made it possible to develop increasingly realistic humanoid robots and animated characters, thereby reshaping human–technology interactions. This study emphasises the significance of the human face as a central stimulus in social identification, an especially pertinent issue in light of developments in generative image-based artificial intelligence, which demands heightened accuracy in reproducing human features. How we navigate this phenomenon will shape the future of our relationship with emerging technologies.